ANALISIS KINERJA RANTAI PASOK PT SUJ MEDAN - Faiz Ahmad Sibuea; Rita Nurmalina; Amzul Rifin (Universitas Medan Area, 2020)
The poultry industry, especially broilers is the basis of the people's economy which has high potential in increasing inclusive economic growth. In addition, it can also be studied from the product distribution side, from the point of producer to the end consumer. One of the companies engaged in the production of broiler broilers is PT SUJ. The purpose of this study is to analyze the performance of farmer and company supply chains using the Supply Chain Operational Reference (SCOR) model approach with regard to internal and external attributes. The results showed that PT SUJ has four institutions involved in marketing broiler chickens, namely breeder partners, companies, brokers / agents and consumers. For measuring supply chain performance, the results of measuring the performance of broiler broiler supply chains at the level of partner farmers on the attributes of responsiveness and flexibility have achieved the best performance position (superior). However, for the attributes of reliability and assets are still at the level of advantage. Meanwhile, the value of chicken supply chain performance for the broiler company level on the attributes of reliability, responsiveness and flexibilty has achieved the best performance (superior). However, for attributes the company's assets only achieve a good position (advantage). Generally, the performance of broiler chicken supply chains is good at the farmer and company level.